PENGARUH DIGITAL COMPLAINT HANDLING TERHADAP KUALITAS PELAYANAN DAN KEPUASAN PELANGGAN: STUDI PADA PT PLN (PERSERO) ULP HELVETIA - Desmon Gunadi Siagian; Katrin Jenny Sirait; Jamardua Haro; Jenny Sari Tarigan; John Sihar Manurung (ITB AAS Indonesia Surakarta, 2026)
Digital transformation in customer complaint handling has become a strategic necessity for public service providers, including PT PLN (Persero). This study aims to examine the effect of Digital Complaint Handling on Service Quality and Customer Satisfaction, as well as to analyze the mediating role of Service Quality among customers of PLN ULP Helvetia. A quantitative approach was employed using PLS-SEM analysis on 150 respondents who had utilized the Chempion Mobile application. The results indicate that Digital Complaint Handling significantly influences Service Quality (β = 0.78) and Customer Satisfaction (β = 0.31). Furthermore, Service Quality significantly affects Customer Satisfaction (β = 0.62). The mediation analysis reveals that Service Quality partially mediates the relationship between Digital Complaint Handling and Customer Satisfaction, with an indirect effect of 0.484 and a VAF value of 61%. These findings confirm that the success of digital service initiatives is determined not only by technological implementation but also by the extent to which they improve overall service quality. The study suggests that optimizing digital service features and strengthening service quality dimensions are crucial strategies for enhancing customer satisfaction.